2015
DOI: 10.1080/01694243.2015.1018731
|View full text |Cite
|
Sign up to set email alerts
|

The significance of cadherin for cell–cell interactions and cell adhesions on biomaterials

Abstract: Cadherins are surface glycoproteins on plasma membranes and exist in many forms: T-cadherin, neuronal cadherin (N-cadherin), epithelial cadherin (E-cadherin), and vascular endothelial (VE-cadherin). Cadherins play critical roles in cell-cell interactions and are involved in multiple functions related to cell growth and proliferation. Findings from numerous reports have indicated that VE-cadherin regulates the remodeling, gating, and maturation of vascular vessels. The surface morphology of materials also impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Results of scanning electron microscopy revealed that the width of the parallel grooves produced by the plasma treatment was increased following treatment with C (250 W) for 5 min compared with that on samples A (150 W), B (200 W) or D (300 W). Although it has been reported that such increases in grooves can allow increased cell adhesion and promote cell‐cell interactions, under the influence of fluid flow, the cellular phospholipid bilayer structure would initiate cell movement within the groove along with the direction of flow thereby weakening the potential for cell adhesion to the surface of the material. When compared with C (250 W), the grooves on the surfaces of samples B (200 W) and D (300 W) were more narrow and dense, which can, in part, increase the capacity for cell contact, and thus adhesion, to the surface of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…Results of scanning electron microscopy revealed that the width of the parallel grooves produced by the plasma treatment was increased following treatment with C (250 W) for 5 min compared with that on samples A (150 W), B (200 W) or D (300 W). Although it has been reported that such increases in grooves can allow increased cell adhesion and promote cell‐cell interactions, under the influence of fluid flow, the cellular phospholipid bilayer structure would initiate cell movement within the groove along with the direction of flow thereby weakening the potential for cell adhesion to the surface of the material. When compared with C (250 W), the grooves on the surfaces of samples B (200 W) and D (300 W) were more narrow and dense, which can, in part, increase the capacity for cell contact, and thus adhesion, to the surface of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…Results from prior research have demonstrated that a hydrophilic surface on a material may be beneficial for cell adhesion and proliferation. 9,35 Moreover, the pore size, pore structure, material's permeability, and physical/chemical properties not only impact cell proliferation but also can control the direction of cell growth, as has been demonstrated in an artificial nerve guide conduit. 36 It is well known that hydrophilicity/hydrophobicity can be influenced by the surface chemistry, while the roughness ratio and topological structure can also influence the wettability of the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a considerable amount of effort has been directed at improving the biocompatibility of biomaterials in order to reduce such complications. Some examples of these attempts have included a layer by layer assembly, surface grafting and alterations in surface morphology . Ranella et al, utilized the microstructure of nanosilicon materials as an approach to impact cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell adhesion always begins with adhesion of the extracellular matrix (ECM), which plays an important role in the regulation of cell‐cell interaction and cell‐surface adhesion . Nonetheless, when using biomaterials, this process can oftentimes be influenced by the structure of the textile material.…”
Section: Introductionmentioning
confidence: 99%